Ecological genetics of freshwater fish: a short review of the genotype–phenotype connection - Vidal, O.; García–Marín, J. L. (Animal Biodiversity and Conservation, 2011)
Molecular ecology or ecological genetics is an expanding application of population genetics which has flourished in the last two decades but it is dominated by systematic and phylogeographic studies, with relatively little emphasis on the study of the genetic basis of the process of adaptation to different ecological conditions. The relationship between genotype and adaptive phenotypes is weak because populations are often difficult to quantify and experiments are logistically challenging or unfeasible. Interestingly, in freshwater fish, studies to characterize the genetic architecture of adaptive traits are not as rare as in other vertebrate groups. In this review, we summarize the few cases where the relationship between the ecology and genetics of freshwater fish is more developed, namely the relationship between genetic markers and ecological phenotypes.